A passive heat maintenance strategy implemented during a simulated half-time improves lower body power output and repeated sprint ability in professional Rugby Union Players. - Russell, M.; West, D. J.; Briggs, M. A.; Bracken, R. M.; Cook, C. J.; Giroud, T.; Gill, N.; Kilduff, L. P. (PLOS ONE, 2015)
Reduced physical performance has been observed following the half-time period in team sports players, likely due to a decrease in muscle temperature during this period. We examined the effects of a passive heat maintenance strategy employed between successive exercise bouts on core temperature (Tcore) and subsequent exercise performance. Eighteen professional Rugby Union players completed this randomised and counter-balanced study. After a standardised warm-up (WU) and 15 min of rest, players completed a repeated sprint test (RSSA 1) and countermovement jumps (CMJ). Thereafter, in normal training attire (Control) or a survival jacket (Passive), players rested for a further 15 min (simulating a typical half-time) before performing a second RSSA (RSSA 2) and CMJ's. Measurements of Tcore were taken at baseline, post-WU, pre-RSSA 1, post-RSSA 1 and pre-RSSA 2. Peak power output (PPO) and repeated sprint ability was assessed before and after the simulated half-time. Similar Tcore responses were observed between conditions at baseline (Control: 37.06±0.05°C; Passive: 37.03±0.05°C) and for all other Tcore measurements taken before half-time. After the simulated half-time, the decline in Tcore was lower (-0.74±0.08% vs. -1.54±0.06%, p<0.001) and PPO was higher (5610±105 W vs. 5440±105 W, p<0.001) in the Passive versus Control condition. The decline in PPO over half-time was related to the decline in Tcore (r = 0.632, p = 0.005). In RSSA 2, best, mean and total sprint times were 1.39±0.17% (p<0.001), 0.55±0.06% (p<0.001) and 0.55±0.06% (p<0.001) faster for Passive versus Control. Passive heat maintenance reduced declines in Tcore that were observed during a simulated half-time period and improved subsequent PPO and repeated sprint ability in professional Rugby Union players. A Passive Heat Maintenance Strategy Implemented during a Simulated Half-Time Improves Lower Body Power Output and Repeated Sprint Ability in Professional Rugby Union Players..